LEMARI PENDINGIN PORTABLE UNTUK PENYIMPANAN AIR SUSU IBU (ASI) MENGGUNAKAN TERMOELEKTRIK - Muhammad Gilang Suryanata; Khairi Ibnutama (STMIK Royal, 2020)
Abstract: The importance of breast milk as the main intake of the baby has become common knowledge for every breastfeeding mother. Exclusive breastfeeding is recommended by the government and WHO for breastfeeding mothers until the baby is two years old. The main obstacle to exclusive breastfeeding for babies is generally caused by the short resistance of breast milk to temperature factors, where breast milk can only last for less than four hours at room temperature. Therefore, a study was made in the form of a portable refrigerator design which aims to make breastfeeding mothers able to store breast milk longer, especially for career women who spend part of their time outside the home and not with babies. The refrigerator is made using a Peltier module with a thermoelectric working concept that is powered by an electric current or a battery so that it can be taken on trips. Keywords: Arduino; Breast Milk; Cooler; Peltier; Thermoelectric Abstrak: Pentingnya ASI sebagai asupan utama bayi telah menjadi pengetahuan umum bagi setiap ibu menyusui. Pemberian ASI ekslusif dianjurkan oleh pemerintah dan WHO kepada ibu menyusui sampai kurun waktu umur bayi dua tahun. Kendala utama terhambatnya pemberian ASI ekslusif kepada bayi umumnya disebabkan oleh daya tahan ASI yang singkat terhadap faktor suhu, dimana ASI hanya mampu bertahan selama kurang dari empat jam pada suhu ruangan. Oleh sebab itu dibuatlah penelitian berupa rancang bangun lemari pendingin portable yang bertujuan agar ibu menyusui dapat menyimpan ASI lebih lama, terutama bagi wanita karir yang sebagian waktunya diluar rumah dan tidak bersama bayi. Lemari pendingin dibuat menggunakan modul Peltier dengan konsep kerja termoelektrik yang ditenagai arus listrik atau baterai sehingga dapat dibawa dalam perjalanan. Kata kunci: Arduino; ASI; Peltier; Pendingin; Termoelektrik